Should ipratropium bromide be added to beta-agonists in treatment of acute severe asthma? - Higgins, R; Stradling, JR; Lane, D (1988)
In a double-blind randomized trial, 40 patients with acute severe asthma were given either nebulized salbutamol, 5 mg, or salbutamol, 5 mg mixed with ipratropium bromide 500 micrograms, on admission to hospital and again two hours later. There was no significant difference between the mean peak flows of the two treatment groups at any time. However, two hours after each treatment, there were fewer subjects in the ipratropium and salbutamol group whose peak flow rates had fallen back toward baseline levels than in the salbutamol only treatment group. Thus, although ipratropium did not improve the overall maximal bronchodilator response, it may have prolonged the duration of the response, which would be a clinically useful effect.